RANCANG BANGUN APLIKASI BROADCASTING SYSTEM ROMA CLUB INDONESIA REGIONAL SEMARANG (Information Technology and Telematics, 2015)
Abstract : Increasingly  rapid  development of  the  internet is  also followed by rapid technological developments. Now almost all walks of life have a smartphone,  computer tables and other mobile devices. Mobile devices are no longer a luxury, now the device has become a necessity and a tool to support the activities. Moreover, mobile devices are able to make an internet connection which is equivalent to a personal computer, so it can be a multifunction device. The   aim   of   the   research   is   to   design   and   build applications broadcasting system Rome Club Indonesia Regional Information Semarang with bulk SMS system with models wearing their use of the mobile phone WAP browser. Dissemination of information via SMS can be done by the coordinator and liaison RCIRS. The difference is added to the information activities coordinator will only be delivered via SMS to the management ranks RCIRS while activity information submitted by the public relations department RCIRS  will be delivered  via  SMS  to all members RCIRS. Members can check information via SMS by using keywords (keywords) that is sent to the SMS server number and will immediately get a reply (reply) SMS in accordance with the key word. For example, to check the status of RCIRS membership, members can send an SMS with the keyword "info". The downside of making this application is in its required to use the SMS server on a computer / laptop that is connected to the SMS modem and modem internet.   Kata Kunci : Broadcasting system, roma club semarang, SMS